Heaven's prisoners - Burke, James Lee, 1936-; Hammer, Mark. (Prince Frederick, Md. : Recorded Books, 1996)
Robicheaux, a recovering alcoholic, has retired to bayou country when a small plane full of passengers -- and trouble -- drops out of the sky near his boat. But as he rescues the only survivor, a girl he names Alafair, the crash soon plunges him into a netherworld of murder and deception. Trapped by events he cannot control, the usually quiet and gentle Robicheaux protects himself and his loved ones the only way he knows how: with a fist and a gun.
In container (17 cm.).
Title from container.
"Unabridged Mystery"--Container.
"A Dave Robicheaux Mystery"--Container.
"With tracks every 3 minutes for easy book marking"--Container.
Narrated by Mark Hammer.
Keywords: Robicheaux, Dave (Fictitious character) -- Fiction; Private investigators -- Louisiana -- Fiction; Audiobooks; Louisiana -- Fiction; Mystery fiction